Forward-looking Component in Consumers' Expectations and the Central Bank's Forecast: Some Evidence for European Countries - Magdalena Szyszko; Aleksandra Rutkowska (Institute of Economic Research (IER), 2017)
Modern monetary policy should be expectations-oriented. The best way to influence expectations operationally is to use inflation forecasts. As different ways of revealing central bank's intentions exist, a simple research question arises. Does the forward-looking (FL) component of consumers' expectations depend on the way in which the forecast is revealed and used by the central bank? The main purpose of the article is to address the mentioned above question. The research hypothesis assumes that the forecasting system which is more transparent together with a greater central banks' consistency in inflation forecast targeting (IFT) result in more FL consumers' expectations. We quantified inflation expectations of consumers on the basis of survey responses (EC Business and Consumer Surveys) with Carlson and Parkin method. When it was needed we applied its version adjusted for deflation. Then, we checked the rationality of consumer expectations (tests for their unbiasedness and orthogonality) and the degree of their FL by means of regression models. Finally, we used the IFT index, which we have elaborated ourselves in order to assess the transparency of the forecasting system and the central banks' commitment to IFT. The research covers Czechia, Hungary, Romania, Poland, Sweden and the UK and the time span of 2001-2016. For Poland, Sweden and the UK more IFT commitment and transparency was related to more consumers' forward-lookingness. For Czechia we found low level of FL in expectations but high level of IFT commitment. We did not succeed in estimating the extent of FL for the two remaining countries due to structural breaks in their monetary policy. The following study contributes to the literature on inflation forecast targeting as it presents the novel empirical application of IFT index for the expectations analysis.
Keywords: E58; E43; 330; inflation forecast; inflation forecast targeting; consumers expectations; forward-lookingness of expectations